In vivo glia‐to‐neuron conversion: pitfalls and solutions - Wang, Lei‐Lei; Zhang, Chun‐Li (Developmental neurobiology (Hoboken, N.J.), 2022)
Neuron loss and disruption of neural circuits are associated with many neurological conditions. A key question is how to rebuild neural circuits for functional improvements. In vivo glia‐to‐neuron (GtN) conversion emerges as a potential solution for regeneration‐based therapeutics. This approach takes advantage of the regenerative ability of resident glial cells to produce new neurons through cell fate reprogramming. Significant progress has been made over the years in this emerging field. However, inappropriate analysis often leads to misleading conclusions that create confusion and hype. In this perspective, we point out the most salient pitfalls associated with some recent studies and provide solutions to prevent them in the future. The goal is to foster healthy development of this promising field and lay a solid cellular foundation for future regeneration‐based medicine.